A constituição da profissionalidade docente: os efeitos do campo de tensão do contexto escolar sobre os professores - Alves, Cristovam da Silva (2012)
This research aims at investigating the constitution of teaching professionality under the action of work contexts influenced by quality indicators Ideb e Idesp and existing dispositions in the school. The study was made in two public schools of basic education (final years) and high school, located in the metropolitan region of São Paulo, subordinated to two different Educational Directories of the State System. Documents and information from 2007, 2008 and 2009 were collected, and questionaires and semi-structured interviews were carried on to a sample of 10 percent of the teachers from those schools: four teachers from the smaller school and nine teachers from the bigger one. Directors and pedagogical coordinator teachers from those schools were also interviewed. The theoretical reference of this research was the studies of Roldão (2005 and 2007) about the teaching professionality descriptors, and it is also upheld by Gimeno Sacristán (1995), Nóvoa (1995, 2008 and 2009), Reis Monteiro (2008) and Morgado (2005). The collected data were analyzed with basis on the categories: position specificity , specific knowledge , power of decision , collective organization and professional development . The pertinence of the professionality descriptors was confirmed to help in understanding the teaching professionality constitution processes. The data analysis allowed the conclusion that the teaching professionality is about a complex process, dependent of internal and external factors to the work context and the disposition of professional insertion, the perennial of the manager and teaching teams in schools and the organization of teacher collectiveness showed themselves with potential to increase or subtract the professionality